The chosen few: Mycobacterium tuberculosis isolates for IMPAc-TB - Larsen, Sasha E.; Abdelaal, Hazem F. M.; Plumlee, Courtney R.; Cohen, Sara B.; Kim, Ho D.; Barrett, Holly W.; Liu, Qingyun; Harband, Matthew H.; Berube, Bryan J.; Baldwin, Susan L.; Fortune, Sarah M.; Urdahl, Kevin B.; et al. (Frontiers in Immunology, 2024)
The three programs that make up the Immune Mechanisms of Protection Against Mycobacterium tuberculosis Centers (IMPAc-TB) had to prioritize and select strains to be leveraged for this work. The CASCADE team based at Seattle Children’s Research Institute are leveraging M.tb H37Rv, M.tb CDC1551, and M.tb SA161. The HI-IMPACT team based at Harvard T.H. Chan School of Public Health, Boston have selected M.tb Erdman as well as a novel clinical isolate recently characterized during a longitudinal study in Peru. The PHOENIX team also based at Seattle Children’s Research Institute, have selected M.tb HN878 and M.tb Erdman as their isolates of choice. Here we describe original source isolation, genomic references, key virulence characteristics, and relevant tools that make these isolates attractive for use. The global context for M.tb lineage 2 and 4 selection is reviewed including what is known about their relative abundance and acquisition of drug resistance. Host-pathogen interactions seem driven by genomic differences on each side and these play an important role in pathogenesis and immunity. The few M.tb strains chosen for this work do not reflect the vast genomic diversity within this species. They do, however, provide specific virulence, pathology and growth kinetics of interest to the consortium. The strains selected should not be considered as “representative” of the growing available array of M.tb isolates, but rather tools that are being used to address key outstanding questions in the field.